Employability forecast among construction management from the employer's perspective in Malaysia construction industry / Farrah Norrizah Mohd Yussof, Haifa Afieqah Hasbi and Emma Marinie Ahmad Zawawi - MOhd, Yussof; Hasbi, Haifa Afieqah; Ahmad Zawawi, Emma Marinie (UiTM Press, 2021)
The tertiary education institutions in Malaysia are facing increasing demands from employers and stakeholders to ensure the graduates to be equipped with relevant skillset needed to secure a placement in the industry. The question arises, what are the skillsets required by employers contribute to the research gap which led to a comprehensive understanding on the expectation of employers towards the graduate's employability. This study determined the employers' perspective skills by referring to five (5) field of employment consist of Developer, Contractor, Consultant, Supplier and Entrepreneur which consume of 57 (38%) respondents from 150 questionnaires distributed both on-site and on-line survey using random sampling technique. The content was referred on the program offered by Bachelor of Science in Construction Management, Universiti Teknologi MARA (UiTM). An exploratory factor analysis (EFA) was conducted using six (6) main categories of courses on hard skill to achieve the objective one and seven (7) soft skills to accomplish objective two. The finding indicates Project Management, Measurement and Estimating and Legal Study knowledge of hard skill critically required, whilst, interpersonal and communication soft skill is crucially needed. Those skills reveal as the fundamental knowledge in handling a construction works. In summary, this study able to facilitate the gap between graduates' skills and employers' expectation by providing a sufficient guidance platform referring to the respective field of employment as well as provides a significance implication to the educational institutions to align the program outcome toward the needs of the industry.